Analisis Preferensi Mahasiswa dalam Menggunakan Qris Sebagai Teknologi Pembayaran - Fitri Emiliyana; Salamatun Asakdiyah; Aftoni Sutanto (Jurnal Perilaku dan Strategi Bisnis, 2024)
This study aims to analyze student preferences in using QRIS as a payment technology. However, there are several problems faced by students of Universitas 'Aisyiyah Yogyakarta in using QRIS such as internet network limitations, scanning errors, transaction failures, loss of privacy, fraud, and loss of funds. In addition, students also face social problems such as limited knowledge, access, and dependence on cash. Therefore, this study aims to identify student preferences in using QRIS and overcome the problems faced. Data analysis was carried out using SPSS software to test the hypothesis proposed. This research is a type of quantitative research using primary data through the distribution of questionnaires. The population in this study is students of 'Aisyiyah University Yogyakarta who use QRIS. The sample in this study is part of the population that uses QRIS totaling 234 respondents. This study uses the Nonprobability Sampling  method with a purposive sampling technique. The results of the analysis show that convenience and benefits have a significant influence on student preferences. Meanwhile, the risk did not have a significant effect. The determination coefficient (R2) obtained at 44.7% shows that the three independent variables are able to explain 44.7% of the factors that affect the preferences of students of Universitas 'Aisyiyah Yogyakarta in using QRIS as a payment technique.